Representation of Minangkabau Women in the Formation of Digital Culture (A Critical Ethnographic Study of the Entrepreneurship Sector) - Reni Novia; Rizki Briandana; Heri Budiyanto (Baca Dulu Publisher, 2026)
Title: Representation of Minangkabau Women in the formation of digital Culture : A Critical Etnographic Study Of the entreupreunership. Purpose: This study aims to explore the transformation and representation of Minangkabau cultural identity within the framework of the digital economy. Specifically, this research formulates the study on how Minangkabau women entrepreneurs, who are traditionally rooted in a matrilineal system, negotiate cultural values when engaging in modern digital business practices.Methodology: This study uses a Systematic Literature Review (SLR) with the PRISMA approach. Data was synthesized from 30 high-quality articles (2016-2026) indexed in Scopus, SINTA, and Google Scholar, focusing on the intersection of matrilineality, gender roles, and digital entrepreneurship.Results: Data synthesis reveals three main